Transformative Leadership: The Principal's Role in Curriculum Innovation for Student Talent and Interest Development - Faozi, Ahmad; Purwanto, Nurtanio Agus (Jurnal Pedagogi dan Pembelajaran, 2024)
The primary issue in this study is the lack of effective development of students' talents and interests within the education curriculum and the need for innovation to improve the quality of education. This research aims to analyze key elements of innovative curriculum planning and evaluate its effectiveness in fostering students' potential. The study employs a qualitative descriptive approach with a case study design. The research subjects include the school principal, 10 teachers, 5 administrative staff members, 5 school committee members, and 20 parents of students. Data were collected through semi-structured interviews, participatory observations, and document analysis. Thematic analysis was used to identify patterns and key themes within the data. The findings indicate that key elements of innovative curriculum planning include strong school policies and commitment, additional instructional hours, academic guidance programs, student skills documentation, supplementary language tutoring, extracurricular activities, and computer training. The study concludes that structured and innovative curriculum planning can significantly enhance the development of students' talents and interests. The implications of this research underscore the importance of collaboration among all stakeholders in the curriculum planning and evaluation process to achieve optimal educational outcomes.